Pelayanan Kesehatan Di Era Otonomi Daerah Penelitian di Kabupaten Sleman = Health Service in the Era of Regional Autonomy A Research In Sleman Regency - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT This research aims to understand impacts of regional autonomy and decentralization to the quality of health service and community accesibility in using health service facilities. This research uses qualitative method in collecting primary data by in-depth interview with those involved in policy making and health servicing as well as secondary data It includes that the implementation of health decentralization in the era of regional autonomy is conducted on three aspects. The first aspect involves institutional and human resources aspect. Although the government of Sleman Regency has made hard efforts to develop institutions and human resources to respond to health decentralization demand, their policy still cannot advance institution's efficiency and effectiveness. This can be seen from the dominant role the executive plays in making regional rules on health service (which in turn may cause bias of executive interest), weak legislative control to policy implementation, and lack of paramedics (who infact have a very strategic role in strengthening community's level of health condition). In the second aspect of funding, it is found that the government of Sleman Regency's commitment in the development of health sector is not convincing. On one side, this can be seen from the amount given in the regional budget to health sector, which remains the same before and after regional autonomy. The amount even dropped when regional autonomy began. On the other side, facts have shown that health sector is among top sectors to increase PAD. As for the third aspect of health service, it is good to note that the quality of health service delivered by government and the private sector has shown some progress, Nevertheless, there are still some indicators that need to be enhanced. The poor can use health service facilities through the central government's program of JPK-Gakin. Despite this fact, not all parts of the poor have received their benefits. This program still cannot drive for community's self-health